2014
DOI: 10.3906/kim-1303-20
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of new pyrazole and antibacterial pyrazolopyrimidine derivatives

Abstract: 3-Substituted-1-phenyl-1 H -pyrazolo[3,4-d ]pyrimidin-4-amines 2a-c were synthesized by treating 5-aminopyrazole-4-carbonitriles 1a-c with formamide. The reactivity of compounds 1a-c towards some cyclic anhydrides was studied. The condensation of 5-aminopyrazole-4-carbonitrile 1b with triethylorthoformate gives imidate 7b, which reacts with a series of primary amines and leads to pyrazolo[3,4-d ]pyrimidine-4-amines 9 and 10. The reaction of imidate 7b with ammonia and hydroxylamine afforded pyrazolopyrimidine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Pyrazole derivatives have great importance in the medicinal and pesticide fields [13,14,15], due to their broad range of biological activity [16,17,18]. The molecules of many modern drugs with antiphlogistic, antidiabetic, analgesic, and acaricidal activity in medicine [19] and herbicidal [20,21,22], antibacterial [23,24,25], acaricidal and insecticide [26,27] in the pesticide area contain pyrazole rings as a structural fragment. As shown in Figure 1, several pyrazole derivative products have been launched or announced, and they all contain several common structural features that are essential to their activity, including an amide bond, pyrazole and an aromatic ring attached to the carbonyl of the amide bond.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrazole derivatives have great importance in the medicinal and pesticide fields [13,14,15], due to their broad range of biological activity [16,17,18]. The molecules of many modern drugs with antiphlogistic, antidiabetic, analgesic, and acaricidal activity in medicine [19] and herbicidal [20,21,22], antibacterial [23,24,25], acaricidal and insecticide [26,27] in the pesticide area contain pyrazole rings as a structural fragment. As shown in Figure 1, several pyrazole derivative products have been launched or announced, and they all contain several common structural features that are essential to their activity, including an amide bond, pyrazole and an aromatic ring attached to the carbonyl of the amide bond.…”
Section: Introductionmentioning
confidence: 99%
“…The behavior of nitrile 1 toward secondary amine such as piperidine, as N ‐nucleophile, has been also investigated for a facile synthetic route to attain enaminonitrile analogs. Enaminonitriles are versatile reagents, and their chemistry has recently received considerable attention as precursors to otherwise not readily obtainable heteroaromatics . We have recently reviewed the chemistry of the synthesis and application of heterocycles derived from enaminonitriles .…”
Section: Resultsmentioning
confidence: 99%
“…The formation of exclusively C( 6)-isomer 133 by this route indicates regioselective condensation of DMF-DEA with the free amino group of the 4-carboxamidine substituent of imidazole 131 99 as shown in Scheme 44. Ben Jannet et al 100 obtained the corresponding ethoxymethyleneamino derivative 136 by the reaction of 5-aminopyrazole-4-carbonitrile 135 with TEOF 101 and demonstrated that imidate 136 reacted at its two electrophilic centers with aliphatic amines 116 to form pyrazolopyrimidines 138a-c in two steps via intermediates 137a-c. In the first step, the condensation of imidate 136 with amines 116 in EtOH in the presence of a catalytic amount of AcOH leads to intermediate compounds 137a-c due to the nucleophilic attack of the amino group at the imide carbon atom.…”
Section: Scheme 43mentioning
confidence: 99%